2021
DOI: 10.1080/2331186x.2021.1940631
|View full text |Cite
|
Sign up to set email alerts
|

Reading Development among Swedish Children: The Importance of Contextual Resources and Language Ability

Abstract: Language abilities in preschool years, including those measured with letter knowledge, are predictors of reading development in later school years. The aim of this study was to investigate variation in children's language abilities before they started school in relation to gender and neighborhood level socioeconomic status (SES). Schools from three municipalities with varied resources and living conditions participated in this study. The participants were 231 children 4-6 years old (girls n = 117, boys n = 114… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…For example, a Swedish cross-sectional study with children four to six years old (a subset of children in the present study) showed that those children attending preschools in economically advantaged areas had elevated letter recognition and more rapid naming of objects (i.e., indicators of linguistic and reading development), in comparison to children attending preschool in disadvantaged areas (Herkner et al, 2021). In addition, a recent Swedish report suggests that the proportion of children who are eligible for high school at 16 years of age, as well as those who complete a high school education with a degree are higher among children who live in economically advantaged neighborhoods relative to children living in economically disadvantaged areas (Delegationen mot segregation, 2022).…”
Section: Introductionmentioning
confidence: 51%
“…For example, a Swedish cross-sectional study with children four to six years old (a subset of children in the present study) showed that those children attending preschools in economically advantaged areas had elevated letter recognition and more rapid naming of objects (i.e., indicators of linguistic and reading development), in comparison to children attending preschool in disadvantaged areas (Herkner et al, 2021). In addition, a recent Swedish report suggests that the proportion of children who are eligible for high school at 16 years of age, as well as those who complete a high school education with a degree are higher among children who live in economically advantaged neighborhoods relative to children living in economically disadvantaged areas (Delegationen mot segregation, 2022).…”
Section: Introductionmentioning
confidence: 51%
“…Although they increase with age (Bouchière et al, 2010), naming scores for lowercase letters were expected to be lower than for uppercase letters (Evans et al, 2006;Helal, 2012;Treiman & Kessler, 2004). Despite the consistent superiority of girls' naming scores over boys', the gender effect failed to reach significance in Study 1, demonstrating its fragility (Ecalle et al, 2020;Herkner et al, 2021;Sigmundsson et al, 2020;Treiman et al, 2007). In this context, it remains an open question whether gender affects lowercase letter naming scores.…”
Section: Study 2: Knowledge Of Lowercase Printed and Cursive Letter N...mentioning
confidence: 95%
“…However, conflicting findings have been reported. Some experiments indicated that girls outperformed boys (Ecalle et al, 2020;Evans et al, 2006;Sigmundsson et al, 2020;Treiman et al, 2007), while others reported no significant difference between girls and boys (Herkner et al, 2021;Worden & Boettcher, 1990). Further research therefore seems warranted.…”
Section: Lnk and Child-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the national reports aim to describe the quality of preschool and aspects to improve it, knowledge is limited concerning the actual performance of the children attending preschool in general, particularly those within the areas of disadvantage. Although the most recent years have provided new insights about literacy development in community samples (e.g., Herkner et al, 2021), there is a dearth of studies focusing on the early language skills of additional language learners in the early childhood setting in Sweden.…”
Section: Our Contextmentioning
confidence: 99%